A mechanical investigation of perfluorooctane acid adsorption by engineered biochar. (15th March 2022) - Wu, Yudi; Qi, Lin; Chen, Gang
Abstract: Biochar has been engineered to enhance its adsorption for perfluorooctane acid (PFOA). In this study, adsorption of PFOA by engineered biochar derived from feedstocks of switchgrass, water oak leaves and biosolid was investigated. Biosolid biochar had better PFOA adsorption than those of switchgrass and water oak leaves because it had higher contents of O% (26.16–36.59%) and S% (1.03–3.68%) as well as higher metal contents such as Ca, Cu, and Fe. To enhance PFOA adsorption, the biochar was engineered with additives of FeCl3 and carbon nanotube. Carbon nanotube significantly enhanced the surface area of all the engineered biochar by up to 8.5-fold. On the other hand, FeCl3 increased the porosity, pore volume and surface area of plant-based biochar (i.e., switchgrass and water oak leaves). Three adsorption mechanisms, electrostatic interaction, hydrogen bonding, and hydrophobic interaction were responsible for PFOA adsorption. Based on the results of this study, electrostatic interaction was found to play the most important role. Thermodynamic analysis indicated the spontaneous and exothermic reactions occurred during the PFOA adsorption and X-ray spectroscopy results demonstrated that impregnated Fe exhibited as disordered cluster crystals on the surface of engineered biochar. It was concluded that Fe-engineered biochar could significantly improve PFOA adsorption, which had promising potential applications of PFOA removal during wastewater treatment processes. Graphical abstract: Image 1 Highlight: Biosolid biochar removed highest amount of PFOA than plant-based biochar. FeCl3 impregnation enhanced the PFOA adsorption. Electrostatic interaction is the major mechanism. The effects of physicochemical water properties on PFOA removal were studied.